An investigation into the ways in which art is taught in an English Waldorf Steiner school. (March 2016) - Hallam, Jenny; Egan, Susan; Kirkham, Julie
Highlights: Waldorf Steiner educated children demonstrate superior expressive drawing skills. Little is known about a Waldorf Steiner approach to art. Waldorf Steiner teachers reported satisfaction with their art training and valued art. Waldorf Steiner teachers presented art as a site for personal growth. Waldorf Steiner children receive an education that focuses on the head, heart and hands. Abstract: Children who are educated using a Waldorf Steiner approach demonstrate superior expressive drawing skills (Rose et al., 2011) but little is known about how art is taught within this educational system. Four Waldorf Steiner primary school teachers participated in semi-structured interviews designed to explore the Waldorf Steiner educational philosophy, their training and the ways in which they approach art in the classroom. A social constructionist thematic analysis identified two themes – teacher's experience of art and the teacher and child's approach to art. Within these themes the importance of adequate training which stresses the value of art and gives teachers opportunity to engage in art activities was emphasised. Such training was linked to an effective teaching approach which placed importance on teaching skills and encouraging children to develop their understanding of art through discussion.